Omega-3 Fatty Acids Control Immune Stress in Dairy Cattle - Lokenga Badinga; Cristina Caldari-Torres (EDIS)
Understanding how omega-3 PUFA affect the immune functions of dairy cattle may lead to the development of producer-friendly feeding strategies that will decrease the incidence of diseases and improve reproductive efficiency in dairy cows. This 2-page fact sheet was written by Lokenga Badinga and Cristina Caldari-Torres, and published by the UF Department of Animal Science, July 2011.